PENGARUH BUDIDAYA RUMPUT LAUT TERHADAP MAKROZOOBENTOS YANG BERASOSIASI DENGAN LAMUN DI DESA PUNAGA, KEC. MANGARA BOMBANG, KAB. TAKALAR - Ratnawati, Ratnawati; Batau, Haliah (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Seagrass beds important for habitats for various marine biota, improve marine sediments and can recycle nutrients (NH4, P, N) so that can be utilized by other biota including seaweed. Water quality can directly affect the life of the aquatic biota especially macrozoobentos. Therefore, this study was conducted to determine the effect of seaweed cultivation on the presence of macrozoobenthos associated with seagrass bed. The method in this research is survey. Data obtained and collected through seagrass observation, macrozoobentos observation, and water quality measurement in the field and then continued with sediment and water analysis in the laboratory. Data on the relationship between seaweed cultivation and macrozoobenthos density were made by linear regression. Result of correlation test between macrozoobenthos density to seagrass cover at seaweed cultivation and without seaweed cultivation showed different result. At the seaweed cultivation site shows a positive relationship between seagrass cover to macrozoobenthos density. Otherwise, on site without seaweed cultivation showed a negative relationship between seagrass cover to macrozoobenthos density.Key word: macrozoobenthos, seagrass, seaweed cultivation, water quality, substrat